Amnioinfusion before 26 weeks' gestation for severe fetal growth restriction with oligohydramnios: Preliminary pilot study. Issue 3 (18th November 2013) - Takahashi, Yuichiro; Iwagaki, Shigenori; Chiaki, Rika; Iwasa, Tomotake; Takenaka, Motoki; Kawabata, Ichiro; Itoh, Mitsuaki
Abstract Aim The prognosis for severe fetal growth restriction (FGR) with severe oligohydramnios before 26 weeks' gestation (WG) is currently poor; furthermore, its management is controversial. We report the innovative new management of FGR, such as therapeutic amnioinfusion and tocolysis. Material and Methods For FGR and severe oligohydramnios before 26 WG complicated with absent or reversed umbilical artery end‐diastolic flow velocity and/or deceleration by ultrasonography, we performed transabdominal amnioinfusion with tocolysis. Cases with multiple anomalies were excluded. Survival rate and long‐term prognosis were analyzed. Results Among 570 FGR cases, 18 were included in the study. Mean diagnosis and delivery were at 22.6 ± 2.0 and 28.7 ± 3.3 WG. Median birthweight was 625 g (−4.2 standard deviation). Final survival rate was 11/13 (85%). There were five fetal deaths. In seven cases, oligohydramnios improved. Growth was detected in 10/18 fetuses. Furthermore, 8/8 decelerations, 4/12 cases of reversed umbilical artery end‐diastolic flow velocity, 7/14 cases of brain‐sparing effect, and 6/13 venous Doppler abnormalities were improved. When we detected umbilical cord compression, 8/10 cases were rescued. Eleven infants were followed up for an average of 5 years; one case of cerebral palsy with normal development and 10 cases with intact motor functions without major neurological handicap were confirmed. Conclusions In cases of extremely severe FGR before 26 WG with oligohydramnios and circulatory failure, amnioinfusion might be a promising, innovative tool.